2019
DOI: 10.1037/tep0000244
|View full text |Cite
|
Sign up to set email alerts
|

Growth-promoting supervision: Reflections from women of color psychology trainees.

Abstract: This paper discusses growth-promoting supervisory practices from the perspectives of women of color psychology trainees. Based on three personal narratives, we discuss the unique ways that supervisors invite the multiple salient identities of trainees into the supervisory relationship and engage in a mentorship approach tailored to each trainee. We discuss key themes that emerged across the three narratives: the importance of a supervisor pivoting between the role of the expert and the role of a learner, the v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…Participants reported that in certain contexts men supervisees were less comfortable accepting feedback and emotional support from women, due to socio-cultural norms where men were expected to hold positions of power. This supports the findings of Crigler et al (2013) who propose that maintaining an awareness of power dynamics regarding gender is important for supervision, as the management of power hierarchies is key to creating a safe, trusting, and transparent supervisory relationship (Thomas et al, 2019). Such imbalances in MHPSS work were reported by participants, who stated that while MHPSS is a field with more women working in it, the majority of those in positions of power were men.…”
Section: Discussionsupporting
confidence: 85%
“…Participants reported that in certain contexts men supervisees were less comfortable accepting feedback and emotional support from women, due to socio-cultural norms where men were expected to hold positions of power. This supports the findings of Crigler et al (2013) who propose that maintaining an awareness of power dynamics regarding gender is important for supervision, as the management of power hierarchies is key to creating a safe, trusting, and transparent supervisory relationship (Thomas et al, 2019). Such imbalances in MHPSS work were reported by participants, who stated that while MHPSS is a field with more women working in it, the majority of those in positions of power were men.…”
Section: Discussionsupporting
confidence: 85%
“…When searching for literature to better understand WOC’s experience within the mental health field, most of the articles we were able to locate were either focused on POC or women, whereas there were only a handful of articles that focused on WOC. Based on Thomas et al (2019), negotiating for space in the professional setting is something that supervisors can continuously do, while empowering and advocating for WOC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to ongoing structural discrimination, such inequality is also reflected in higher education. Additionally, the immigration status of some international students might disqualify them from governmental financial aid and restrict their ability to work off campus (Sherry et al, 2010;Thomas et al, 2019). Thus, scholars have suggested that school psychology programs actively recruit minoritized individuals by offering financial support (Goforth et al, 2016;Proctor et al, 2014;Proctor & Romano, 2016).…”
Section: Challenges In Recruitment and Retentionmentioning
confidence: 99%